Mini - social phobia inventory (mini-SPIN): psychometric properties and population based norms of the German version. Issue 1 (December 2017) - Wiltink, Jörg; Kliem, Sören; Michal, Matthias; Subic-Wrana, Claudia; Reiner, Iris; Beutel, Manfred; Brähler, Elmar; Zwerenz, Rüdiger
Abstract Background A short screening for social anxiety disorder is useful in clinical and epidemiological contexts. However, the German version of the short form of the Social Phobia Inventory (mini-SPIN) has not been evaluated yet. Therefore, our aim was to determine reliability, validity and population based norms of the German mini-SPIN. Methods The mini-SPIN was evaluated in a clinical (N = 1254) and in a representative community sample (N = 1274). Clinical diagnoses, the Patient Health Questionnaire depression (PHQ-9) and somatization modules (PHQ-15), the Generalized Anxiety Disorder Scale (GAD-7), the Liebowitz Social Anxiety Scale (LSAS), and the Short-Form-12 Health Survey (SF-12) were used in the clinical sample. In the community sample, participants filled out socio-demographic and health related questions and short versions of the PHQ (PHQ-2, GAD-2, panic item). Internal consistency, test-retest reliability, sensitivity to change, discriminant validity, and convergent validity were examined. Receiver operating characteristic curve analyses were performed to determine cut-off scores. Population based norms were computed from the community sample. Results We found internal consistencies between 0.80 and 0.83. Test-retest correlation was Rho = 0.61; sensitivity to change was comparable to the LSAS. Correlations indicated good convergent and discriminant validity of the mini-SPIN. Strict measurement invariance can be assumed regarding age and gender. Receiver operating characteristic curve analysis suggested a cut-off of 6 or higher for a probable diagnosis of SAD. Conclusions The German version of the mini-SPIN is a reliable and valid instrument. Its brevity makes it valuable for screening and assessing changes of social anxiety in clinical and epidemiological studies.